Aging Adjusted Serum Levels of Parathyroid Hormone and 25-Hydroxyvitamin D in Outpatients of a Tertiary Care Center using Generalized Additive Models for Location, Scale, and Shape - Costa, Tatiana Munhoz da Rocha Lemos; Riechi, Salomão Cury; Petterle, Ricardo Rasmussen; Boritza, Kátia Cristina; Moreira, Carolina Aguiar; Boguszewski, Cesar Luiz; Cochensk, Victoria Zeghbi (Archives of Clinical and Biomedical Research, 2020)
Purpose: Evaluate serum concentrations of 25 hydroxyvitamin D (25OHD), calcium and parathyroid hormone (PTH) in samples obtained from a tertiary hospital, and establish the relationship between them, adjusted for age. Methods: Cross-sectional study, samples by convenience from all 25OHD ordered for outpatients in one year, excluding clinical trials, research protocols, chronic kidney or liver diseases. Calcium corrected for albumin, PTH and 25OHD were measured. 25OHD levels were classified as deficiency (< 20 ng/ml), insufficiency (20-30 ng/ml), or sufficiency (> 30 ng/ml). The relationship between PTH and 25OHD adjusted by age was studied using the semi-parametric GAMLSS regression model (generalized additive models for location, scale, and shape). Results: Samples from 1,031 subjects (82% female, age 53.1 ± 18.4 years) were included, mean 25OHD level was 26.6 ± 13.4 ng/mL, 321 (31.1%) patients were vitamin D deficient, and 409 (39.7%) insufficient. 25OHD had a seasonal variation, with lower levels in winter and spring and higher in summer and fall. PTH was elevated in 393 (38.6%) patients, from these, 2.5% were hypercalcemic and classified as primary hyperparathyroidism (HPT), 19.1% as normocalcemic primary HPT, and 78.4% as secondary HPT. The association of PTH and 25OHD adjusted by age showed that PTH decreased up to the 25OHD level close to 40 ng/mL and remained constant after 45 ng/mL. Conclusion: Outpatients from a tertiary hospital had a high prevalence of vitamin D deficiency, which was influenced by seasonality, the PTH plateau was at a 25OHD level of 40 ng/mL when corrected for age.